PENERAPAN MODEL ASSURE BERBANTUAN MEDIA AUDIO-VISUAL TERHADAP HASIL BELAJAR INFORMATIKA DI MTs MUHAMMADIYAH 20 NATAL - Suha Maisaroh; Liza Efriyanti; Sarwo Derta; Riri Okra (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by the use of a direct-based learning model to be a learning model commonly used by an educator in the teaching and learning process. This learning model approach to learning is still teacher-centered so that students who tend to learn and learn become students in teaching and learning activities carried out in schools. With this, researchers take advantage of technological developments that cannot be separated from society, especially students, namely the use of technology (mobile phones). One of them is by applying the ASSURE model assisted by audio-visual media in learning. The type of research used by the author is quantitative research with experimental methods. The research design used is Posttest-Only Control Group Design. The sample of this study were students of class VII in MTs. Muhammadiyah 20 Christmas. The data collection technique used is the Posttest test. The data analysis technique used is a prerequisite test consisting of a normality test and linearity test and hypothesis testing. Informatics subjects as seen from the results of the Posttest in both the control class and the experimental class. With the application of the ASSURE model assisted by audio-visual media in the experimental class, the average value of 80.90 was obtained which resulted in a higher effect than the application of the conventional model which had an average of 44.66 in the control class. Keywords: Learning Model, ASSURE Model, Informatics.